An Outcome Evaluation of the Indianapolis Community Court. (April 2017) - Grommon, Eric; Hipple, Natalie Kroovand; Ray, Bradley
Seeking to alleviate traditional criminal justice system processing for low-level non-violent crimes, community courts have emerged as a viable alternative. These courts use innovative community-based efforts to address the needs of defendants charged with quality-of-life crimes and attempt to improve the surrounding community. Using a retrospective quasi-experimental design, this research examines recidivism outcomes for a sample of 574 defendants who were referred to the Indianapolis Community Court. Repeated-measures ANOVA models were used to assess 1- and 3-year follow-up intervals. Survival models were used to determine whether significant differences between groups exist on the timing of recidivism events. The analysis revealed no statistically significant differences between those individuals who were processed through community court and those processed through traditional courts. The implications of these findings for future research and community court policy and practice are discussed.